Pelaksanaan Teknik Hypnotherapy (Terapi Dengan Hipnosis) Dalam Pencegahan Masalah Pada Anak Usia Dini - Yusnika Damayanti; Jukarnain Jukarnain; Rizki Amalia; Nunung Suryana Jamin; Leli Leli; Rizki Andita Noviar; M. Khalid Fredy Saputra (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Hypnoparenting is a program for parents who want to educate their children in a more effective way or technique, including how to